(untitled) (Revista Contexto & Educação, 2026)
In education, the use of technology involves everything from the appropriation of technological devices to educational practices under the influence of Artificial Intelligences (AIs) and epistemological debates about the technology-education relationship. In this path, several tools bring different possibilities regarding communicational issues, creation and use of virtual learning environments (Author). In this writing, we reflect on the critical use of technology (Feenberg, 2019, 2015, 2013) in the educational context, through theoretical elaborations that consider the pedagogical and political spheres of the use of technologies. In addition, we aim to propose Feenberg’s critical theory of technology (TCT) (Feenberg, 2019, 2015, 2013) as an explanatory possibility for the relations between technologies and education. In addition, we aim to explore the intersection between philosophy, technology and education through the critical analysis of the formative processes developed by/in educational practices and the teaching and learning processes (Libâneo, 2020, 2010); the historical-cultural theory that the understanding of the relationship between culture, technology and social beings (Vygotsky, 2007); and the analytical reading of the social practices of education in their relationship with technologies through Historical-Critical pedagogy (Saviani, 2015). As results and directions of the reflections and debates developed in this writing, we highlight – to the extent that Feenberg (2019) incorporates philosophical elements of the Frankfurt School, such as Adorno and Marcuse, and establishes a dialogue with Marx, highlighting the role of science and technology in human evolution – the relevance of a critical theory of technology that problematizes deterministic assumptions that disregard the influence of educational, social, political and cultural factors.